Aggregated energy storage for power system frequency control : a finite-time consensus approach - Wang, Yu (2020)
In future power systems, widespread small-scale energy storage systems (ESSs) can be aggregated to provide ancillary services. In this context, a new load frequency control scheme which incorporates the energy storage aggregator (ESA) and its associated disturbance observer is proposed. The disturbance observer is designed to supplement the secondary frequency control for the ESA, therefore the system frequency response and recovery can be improved. Within the ESA, a finite-time leader-follower consensus algorithm is proposed to control the small-scale ESSs via sparse communication networks. This algorithm ensures that the ESA tracks the frequency control signals, while the state-of-charge among each ESS is balanced in finite-time. The external characteristics of the ESA will resemble to that of one large-scale ESS. Numerical examples demonstrate the convergence of the ESA under different communication graphs. The effectiveness of the entire scheme for power system frequency control is validated under a variety of scenarios that include contingency and normal operation.